BATU PULAKI AND ITS IMPLICATIONS FOR THE LIVES OF BALINESE PEOPLE - Eka Suadnyana, Ida Bagus Putu; I Nyoman Miarta Putra (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
Batu Pulaki is a stone that is a manifestation of Bali's natural wealth as well as a heritage in the cultural life of the people of Bali. Knowledge of the types, contents, functions and their relationship with the people in Bali. This study aims to describe in more detail the Batu Pulaki its implications for the lives of Balinese people context of the people of Bayupoh Village. To explain the problem above the author uses a type of qualitative research. In this case, the authors were directly involved in data collection by means of observation, documentation, and interviews with informants in the Pulaki area of Bali. In addition, this research uses types of library data such as books, theses, journals, internet media, and so on that supports research. To answer the problem, researchers used Structural Functional Theory. From the research conducted, the findings were obtained, namely the existence of Pulaki stones in a sacred area in which there is the Agung Pulaki temple and several Pasanakan temples around the Pulaki temple. This shows that the Pulaki region with several temples there as relics of Hindu civilization is a center of social and spiritual activity. Pulaki as a sacred area and Pulaki stone as a symbol of community religious ritual facilities historically and theologically provide an aid in understanding religion to the community. The people of Banyupoh Village use Pulaki stones for pedagingan and panca datu, apart from that the existence of Batu Pulaki is also used as a shrine, as a medium of worship by the Hindu community in Banyupoh Village. In its innovation and development, Pulaki stone has been transformed into several art products such as accessories, water fountains and various types of sculptural art.